Elephant Tower and Tower of the Sun
Description attached: Treasure Island "Steps Out," Night view of a portion of Treasure Island in San Francisco Bay as preliminary, experimental test of the $1,000,000 illumination program get underway. When illumination is completed for the opening of California World's fair next year, the island will appear as a "magic city afloat on the bay."